Integrating experimental and atomistic insights into the rejuvenation of aged binder using bio-based rejuvenators - Kurban, Mustafa; Yalcin, Beyza Furtana; Yilmaz, Mehmet; Akpinar, Sinan; Kok, Baha Vural; Hekim, Seda; Goktas, Fahrettin (Elsevier Sci Ltd, 2026)
This study integrates experimental and computational methods to evaluate the rejuvenation performance of an aged asphalt binder using two novel bio-based additives, 1T and 2T. The aged binder, sourced from reclaimed asphalt pavement (RAP), was modified with 25 wt% of each rejuvenator (denoted as 1T25 and 2T25, respectively). SARA (Saturates, Aromatics, Resins, Asphaltenes) fractionation and colloidal indices were used to assess compositional recovery. Both additives increased aromatic and resin contents while reducing asphaltenes. The 2T-modified binder achieved the highest colloidal stability (Ic = 0.29) and the most pronounced improvement in stability indicators (CI and Ic) among the tested systems. Complementary molecular dynamics (MD) simulations using the COMPASSII force field modeled the structural and thermodynamic behavior of RAP and rejuvenated systems. The 2T25 system exhibited higher density and more compact molecular packing, suggesting stronger cohesive organization and reduced free volume, whereas 1T25 showed greater molecular spacing and flexibility. RDF analysis and converged thermodynamic/structural trajectories (energy, temperature, cell length, and density stabilization) further supported rejuvenator-dependent rearrangement of packing during equilibration. Overall, MD acts as a mechanistic bridge that interprets experimental SARA/CI/Ic trends and supports designoriented development of sustainable rejuvenators.
Keywords: Bio-based rejuvenator; Aged asphalt binder; Molecular dynamics (MD); SARA fractionation; Colloidal stability; Reclaimed asphalt pavement (RAP)